Cultural villages as contexts for mediating culture and mathematics education in the South African curriculum - Sylvia Madusise (Revista Latinoamericana de Etnomatemática, 2015)
Some mathematics educational reform policies indicate that mathematics education should be connected to learners‟ cultures. However, teaching in schools rarely brings the interconnection between mathematics and culture in pedagogically informed ways. Connections are often done superficially; the curriculum in schools lacks content and specific strategies that enable the making of the connections explicit in the context of teaching. The qualitative study from which this paper emerges worked with three mathematics teachers in an attempt to teach mathematics in ways that connect key concepts with culture. Through mathematizing culturally-based activities performed at a cultural village2, two Grade 9 mathematics topics in the South African curriculum were indigenised. A teaching unit on the indigenised topics was designed and implemented in five Grade 9 classes at the same school. The paper demonstrates that the experience of designing, implementing, and reflecting on the intervention study had some positive contribution to the participating teachers‟ pedagogical repertoire. Teachers saw the possibility of using cultural villages as instructional resources for connecting mathematics education to learners‟ cultures in the South African curriculum. I argue that cultural villages can be used as contexts for mediating culture and mathematics education.